Vegetative growth ability of artificial cross pollinated of tea clones - Syahrian, Heri; Rahadi, Vitria Puspita; Ruhaendi, Endi; Santoso, Budi (Research Institute for Tea and Cinchona, 2016)
Vegetative propagation is common system that carried out in tea propagation. Seedling propagation was not reliable due to time consuming and phenotypic variability in seed plant. Despite yield potential, good quality, pest and disease resistant characters, the easy of vegetative propagation is very important character in tea breeding process. The aim of this study is to selected clones that resulted by artificial pollination for an ability of vegetative propagation character. Plant materials that tested in this experiment were the seed from the vegetative propagation of 14 clones, and GMB 7 clone as a control. Randomized Block Design was used in this experiment by 3 replications. The data analysis was ANOVA and Scott Knott test. The result of the experiment showed that clone number 41, 45, 38, 149, X5, X3, 122, 78, and 44, were the easiest clones to be vegetative propagated.